Allelopathic Effects of Verbesina Encelioides Cav - Goel, Usha (Annals of Arid Zone, 2016)
Extracts from various parts of Verbesina encelioides Cav. (Compositae) inhibited seed germination and reduced seedling growth in Tephrosia purpurea Baker, Cassia occidenta/is L. ,Crotolaria medicagnia Lamk. and Indigofera linnaei Ali. Leaf and floral extracts were more toxic than the extract of stem and leachates of root.